REGIONALIZATION OF LUMPED WATER BALANCE MODEL PARAMETERS BASED ON MULTIPLE REGRESSION - Yokoo Y.; Kazama S.; Sawamoto M.; Nishimura H. (My University, 2001)
This study establishes a method for evaluating the coefficients of tank model. First, the model coefficients were optimized using the Standardized Powell Method at 12 watersheds. Then 16 characteristics were derived from geographical information on topography, soil type, geology, and land-use of the basins. Finally, a multiple linear regression model was applied to the relationship between the model coefficients and the basin characteristics. Trial application of the regression equations worked successfully at two different watersheds, suggesting that the coefficients of the tank model could be evaluated based solely on the geographical characteristics of the basin.
Keywords: DAM CATCHMENT; DAIRY RUNOFF SIMULATION; BASEFLOW; PARAMETER EVALUATION; PERMEABILITY